Synthesis of N-acyloxy-1-(dimethoxyp-hosphoryloxy)benzimidates from N-acyloxy-N-chlorobenzamides - Shtamburg, Vasiliy; Штамбург, Василь Георгійович; Klots, Evgen; Клоц, Євген Олександрович; Shtamburg, Vіktor; Штамбург, Віктор Васильович; Anishchenko, Andrey; Аніщенко, Андрій Олександрович; Shishkina, Svitlana; Шишкіна, Світлана Валентинівна; Mazepa, Alexander; Мазепа, Олександр Володимирович; et al. (Дніпровський національний університет імені Олеся Гончара, 2025)
Aim.The objective of this research was to investigate the potential interaction between N-acyloxy-N-chlorobenzamides and trialkylphosphites, along with the characterization of the resulting products' structures. Methods. Employing techniques such as 1H, 31P and 13C NMR spectroscopy, mass spectrometry, and single crystal X-ray diffraction, we have proved that the reaction of N-acyloxy-N-chlorobenzamides with trimethylphosphite in diethyl ether produces N-acyloxy-1-(dimethoxyphosphoryloxy)benzimidates. Our research demonstrates that the reaction between N-acyloxy-N-chlorobenzamides and trialkylphosphites offers a novel approach to synthesize Z-N-acyloxy-1-(dialkoxyphosphoryloxy)benzimidates. This discovery unveils a significant chemical transformation of N-acyloxy-N-chlorobenzamides. The structure of N-acyloxy-1-(dimethoxyphosphoryloxy)benzimidates has been confirmed by 1H, 31P and 13C NMR spectroscopy, mass spectrometry, and XRD study. The study of the N-(4-nitrobenzoyloxy)-1-(dimethoxyphosphoryloxy)benzimidate structure has revealed that the N-(4-nitrobenzoyloxy)-1-(dimethoxyphosphoryloxy)benzimidate is the Z-isomer, with the dimethoxyphosphoryloxy moiety and the N-4-nitrobenzoyloxy group being cis-oriented to the N=C double bond. The ether moiety and the N=C double bond are coplanar, while the dimethoxyphosphoryl substituent is orthogonal to the plane of the N=C double bond. The interaction of N-acyloxy-N-chlorobenzamides with trimethylphosphite has led to a new synthesis of Z-N-acyloxy-1-(dialkoxyphosphoryloxy)benzimidates. The new chemical properties of N-acyloxy-N-chlorobenzamides have been established. The X-ray study of Z-N-4-nitrobenzoyoxy-1-benzimidate has demonstrated the peculiarities of its structure. Notably, an intriguing phenomenon of nitrogen-to-oxygen migration of the dimethoxyphosphoryl group has been observed. Мета. Дослідити можливість взаємодії N-ацилокси-N-хлоробензамідів з триметилфосфітом та будову продуктів цієї реакції. Методи. Мас-спектрометрія, 1H, 31Р та 13C ЯМР спектроскопія, рентгеноструктурний аналіз. Результати. Знайдено, що взаємодія N-ацилокси-N-хлоробензамідів з триметилфосфітом у діетиловому етері призводить до утворення N-ацилокси-1-(диметоксифосфорилокси)бензімідатів. Ми довели, що взаємодіяN-ацилокси-N-хлоробензамідів з триалкілфосфітами є новим засобом синтезу N-ацилокси-1-(диметоксифосфорилокси)бензімідатів. Таким чином встановлено нове цікаве хімічне перетворенняN-алкокси-N-хлоробензамідів. Структуру N-ацилокси-1-(диметоксифосфорилокси)-бензімідатів підтверджено спектрами 1H, 31P і 13C ЯМР, мас-спектрами та рентгеноструктурним аналізом. Згідно з даними рентгеноструктурного аналізу N-(4-нітробензоїлокси)-1-(диметоксифосфорилокси)бензімідату він є Z-ізомером, тобто диметоксифосфорилоксигрупа та N-4-нітробензоїлоксигрупа знаходяться в цис-положенні до подвійного зв’язку N=C. Естерна група та зв'язок N=C є компланарними. (MeO)2P(O)-група розташована ортогонально щодо площини подвійного зв’язку N=C. Висновки. Взаємодія N-ацилокси-N-хлоробензамідів з триметилфосфітом у діетиловому етері за кімнатної температури є новим способом синтезу N-ацилокси-1-(диметоксифосфорилокси)бензімідатів. Було встановлено нові хімічні властивост N-ацилокси-N-хлоробензамідів. РСА дослідження Z-N-4-нітробензоїлокси-1-(диметоксифосфорилокси)бензімідату показало особливості його структури. Встановлено цікавий різновид внутрішньомолекулярної міграції фосфорильної групи з атому азоту на атом кисню.
Синтез N- ацилокси-1-(диметокси-фосфорилокси)бензімі-датів з N-ацилокси-N-хлоробензімідів
Keywords: N-acyloxy-N-chlorobenzamides; N-ацилокси-N-хлоробензаміди; trimethyl phosphite; триметилфосфіт; Z-N-acyloxy-1-(dimethoxyphosphoryloxy)benzimidates; Z-N-ацилокси-1- (диметоксифосфорилокси)бензімідати; nitrogen-to-oxygen migration of dimethoxyphosphoryl moiety; азот-кисень міграція диметоксифосфорильної групи